Author correction: alpha-fetoprotein inhibits autophagy to promote malignant behaviour in hepatocellular carcinoma cells by activating PI3K/AKT/mTOR signalling - Wang, Shanshan; Weng, Honglei (Cell death & disease, 2019)
The correct ordering and designations for corresponding/first authors are as follows: Shanshan Wang1,2*, Mingyue Zhu3, Qiaoyun Wang3, Yuli Hou4, Lei Li5, Honglei Weng6, Yan Zhao4, Dexi Chen1,2, Junli Guo3, Huiguo Ding#5, Mengsen Li#3